The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1080/07347324.2012.718960
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Self-Regulation and Self-Efficacy on Substance Use Abstinence

Abstract: Previous research found that self-regulation and self-efficacy were linked to substance use abstinence. The present study examined the relationships between changes in self-regulation and self-efficacy as predictors of substance use abstinence. A total of 150 adult individuals (62% female; M age = 37.1 SD = 8.1; 38% male) in substance abuse recovery participated in a randomized, longitudinal study comparing a communal housing model versus usual aftercare. Both the change in self-regulation (p = .014) and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 37 publications
(54 reference statements)
3
37
0
3
Order By: Relevance
“…There was a positive and high correlation between the perceived self-regulatory efficacy scale for writing and academic self-efficacy scale. Obtaining a positive and significant correlation between the adapted scale and a scale used for criterion validity shows that the adapted scale has criterion validity (Guler 2012;Erkus, 2011) and this finding is consistent with the previous research findings (Chavarria, Stevens, Jason, & Ferrari, 2012;Ghonsooly & Ghanizade, 2011;Hodges, Stackpole-Hodges, & Cox, 2008).…”
Section: Discussionsupporting
confidence: 82%
“…There was a positive and high correlation between the perceived self-regulatory efficacy scale for writing and academic self-efficacy scale. Obtaining a positive and significant correlation between the adapted scale and a scale used for criterion validity shows that the adapted scale has criterion validity (Guler 2012;Erkus, 2011) and this finding is consistent with the previous research findings (Chavarria, Stevens, Jason, & Ferrari, 2012;Ghonsooly & Ghanizade, 2011;Hodges, Stackpole-Hodges, & Cox, 2008).…”
Section: Discussionsupporting
confidence: 82%
“…For the purpose of this study, the lower score of the two measures was used for each participant. We chose to use the lower score because Oxford House residents are required to abstain from all types of drugs and alcohol, and whichever domain is the weakest link in abstinence self-efficacy is the domain most likely to lead to relapse (Chavarria et al 2012). …”
Section: Methodsmentioning
confidence: 99%
“…The reliability estimates in terms of internal consistency for both the DASE and AASE have been shown to be excellent (Cronbach's alphas = .98 and .99, respectively). Research using binary logistic regression found that the prediction percentage between self-efficacy (measured by the DASE/AASE) and avoiding substance use was 66.1% (Chavarria et al 2012). Lastly, the Short-Form (SF-12) measure, adapted from the SF-36 (Ware, Kosinski & Gandek, 2001) was used in construct validation.…”
Section: Methodsmentioning
confidence: 99%